Axinyssa ambrosia and Axinyssa yumae (Porifera, Halichondrida): two valid sponge species from the Caribbean Sea - Zea, Sven; Valderrama, Diego; Martínez, Ana María (Zootaxa, 2013)
Direct field observations often reveal distinct morphotypes within sponge species that had been described on the basis of preserved material from different locations. The genus Axinyssa von Lendefeld, 1897 was revised for the Caribbean by Diaz et al. (1993), defining a single species, Axinyssa ambrosia (de Laubenfels, 1936), with several junior synonyms, some of which varied in the predominant spicule complement. At Santa Marta, Colombia, we found two morphotypes of Axinyssa living sympatrically, with consistent differences in morphology and spiculation. Revision of types and part of Diaz et al. (1993) material confirmed these differences, leading to the distinction of two species whose valid names are Axinyssa ambrosia and Axinyssa yumae (Pulitzer-Finali, 1986). The purpose of this note is to redescribe these two species.